Cover Picture: Geomechanics and Tunnelling 4/2016. Issue 4 (August 2016) - Unknown
Abstract: After 16 months of tunnelling, the Herrenknecht‐Mixshield (diameter 13.7 m) broke through the target shaft wall on the European side of Istanbul. Launched from the Asian side, with water pressures up to 11 bar the 3.34 km long underpass for the two‐story Eurasia road tunnel was an endurance test for tunnelling technology. The successfully completed drive marks new feasibility standards in tunnel construction. Several of the papers presented in this issue of Geomechanics and Tunnelling deal with the Istanbul Strait Road Crossing Project and highlight different aspects of this major infrastructure project. (photo: Herrenknecht AG) Nach 16 Monaten Vortrieb durchbrach die Herrenknecht‐Mixshield (Durchmesser 13, 7 m) die Zielschachtwand auf der europäischen Seite von Istanbul. Die 3, 34 km lange Unterfahrung für den zweistöckigen Eurasia‐Autotunnel stellte bei Wasserdrücken bis zu 11 bar einen wahren Härtetest für die Tunnelvortriebstechnik dar. Der erfolgreich abgeschlossene Vortrieb markiert neue Machbarkeits‐Standards im Tunnelbau. Einige Beiträge dieser Ausgabe der Geomechancis and Tunnelling befassen sich mit dem Istanbul Strait Road Crossing Project und beleuchten verschiedene Aspekte des Infrastrukturprojekts. (Foto: Herrenknecht AG)